Applications of energy absorption devices - Chen, Ron Jinrong. (2012)
Singapore, having a population of approximately 5.3million living in a small land area, the Government is looking into constructing higher buildings to accommodate the increasing demand of living space. Therefore, as the level of the buildings increase, the risk of escaping in a high rise building is greater when a disaster strike. In order to create more ways of escaping a high rise, commercially there are a number of escape equipment in the market but these devices don’t come cheap.